WEBSITE AS AN ECONOMIC CONCEPT AND A COMPLEX OBJECT OF INTELLECTUAL RIGHT PROPERTY - Goi, V. (Socio-economic relations in the digital society, 2021)
The aim of the article is to study the website as an economic concept, as well as a complex object of intellectual property. The article describes the history of one of the main elements of the digital economy of the website as an economic concept. It is emphasized that all websites have software, an address on the Internet with the appropriate information content. It is established that the website is a product of employment of people of different specialties, ie is an economic concept. Creating a website is a joint effort of different specialists. They all own the copyright of their part of the created intellectual product. And a website is a complex intellectual property that has a certain legal regime and problems of its identification. Based on the nature and content, there is reason to consider a non-elementary website as a complex object, which in these conditions of development of innovative technologies, including digital, gives the fullest intellectual rights to the person who organized the complex object and authors the results of intellectual activity that are part of it. It is argued that it is currently impractical to single out any grounds for granting a website a special copyright object. In general, such regulation is the best, although it requires further research in the development of legislation in the field of complex objects. Prospects for further research lie in a thorough study of the legal regime of websites as objects of intellectual property in order to develop a concept of the most optimal legal regulation of the latter. Analysis of the possibility of using methodological approaches and methods of intellectual property valuation to determine the value of websites, development of methods of valuing the website as a complex object of intellectual property, economic and mathematical model of coordination of website valuation results with different methodological approaches, recommendations on transfer and protection of rights website as a complex object of intellectual property.